Design of Distributed Generation with A Hybrid System in Karimunjawa Island - Gunawan, Gunawan; Alifah, Suryani; Raziqy, Moh. Arif (Institute of Advanced Engineering and Science, 2015)
The current condition, in Karimunjawa Island, is supplied by diesel power with a total power output of 400kW. The number of households in this island is 1545, while the number of electricity customers as many as 850 homes with the local electrification ratio of 55%. With such high load electrification, the generator is only operated from 05.00pm-06.00pm every day to limit the operating costs. Methodology used was the determination of the size of the PV generator capacity based on the percentage of daily generation. The selection of conversion technology with hybrid concept synergizes photovoltaic to be combined with diesel. Loading simulations are performed with HOMER application that provides a variety of features on a variety of configurations and scenarios designed.The first scenario is in the form of giving additional capacity by using the power of 100kW of PV system and at peak load by adding the duration of the day with 5 hours, it is obtained the production of PV of 800kWh/day with the selling price of 3,900;/kWh. The second scenario is in the form of giving additional capacity by using the power of 100kW of PV system at noon for 10 hours and during peak load, it gains total value production of PV with1400kWh/day and distributed to system with a selling price of Rp 3,867/kWh.